Structure and Phylogenetic Analysis of an Endogenous Retrovirus Inserted into the Human Growth Factor Gene Pleiotrophin - Schulte, Anke M. (American Society for Microbiology, 1998)
A human endogenous retrovirus-like element (HERV), flanked by long terminal repeats of 502 and 495 nucleotides is inserted into the human pleiotrophin (PTN) gene upstream of the open reading frame. Based on its Glu-tRNA primer binding site specificity and the location within the PTN gene, we named this element HERV-E.PTN. HERV-E.PTN appears to be a recombined viral element based on its high homology (70 to 86%) in distinct areas to members of two distantly related HERV type C families, HERV-E and retrovirus-like element I (RTVL-I). Furthermore, its pseudogene region is organized from 5′ to 3′ into gag-, pol-, env-, pol-, env-similar sequences. Interestingly, full-length and partial HERV-E.PTN-homologous sequences were found in the human X chromosome, the human hereditary haemochromatosis region, and the BRCA1 pseudogene. Finally, Southern analyses indicate that the HERV-E.PTN element is present in the PTN gene of humans, chimpanzees, and gorillas but not of rhesus monkeys, suggesting that genomic insertion occurred after the separation of monkeys and apes about 25 million years ago.